Governing the child-citizen: 'Let's Move!' as national biopedagogy. Issue 8 (16th November 2016) - Jette, Shannon; Bhagat, Krishna; Andrews, David L.
Abstract : In this paper, we offer a critical examination of Let's Move!, the comprehensive anti-obesity program initiated by the First Lady of the United States, Michelle Obama, that aims to solve the problem of childhood obesity within a generation. We argue that Let's Move! is not just a campaign against obesity but is emblematic of the nature of (and assumptions underpinning) the health education of children in the contemporary United States. Drawing on the concept of 'governmentality, ' we examine how Let's Move! functions as a biopolitical strategy (a solution to the problem of childhood obesity), framed by the political rationalities of neoliberalism. In particular, we identify and explore three interrelated bio-techniques mobilized within, and through, the Let's Move! campaign. First, in an effort to 'responsibilize' citizens, the initiative is framed as a social movement whereby all segments of society can (and should) be empowered to take collective action against childhood obesity. Second, an array of multi-sectoral partnerships, including corporate sponsors and non-profit organizations, are being mobilized, resulting in a range of initiatives underpinned by the rhetoric of consumer choice and responsibility as well as the outsourcing of physical education to private entities. Third, the adoption of standardized fitness testing techniques based on the logic of chronic disease epidemiology, and related notions of 'risk, ' aim to produce the disciplined child-citizen who monitors his/her health goals with the aid of Web 2.0 technologies. In contextualizing Let's Move! in this way, we illustrate how, in line with the soft authoritarian imperatives of the neoliberal enabling state, the campaign functions as a national biopedagogy, working to empower every citizen to be an 'active partner' in the fight against childhood obesity, so as to optimize the health of the next generation and allow them, in the words of Michelle Obama, to 'pursue their dreams.'